IMPLEMENTASI PIJAT OKSITOSIN TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POST PARTUM - Magdalena Limbong; Panua, Husniati A.; Erna Kasim; Nurhayati (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2024)
Mother's Milk (ASI) is the most appropriate nutrition given to newborns until the age of 6 months because at that time the baby's intestines are not yet able to digest food other than breast milk. From a scientific point of view it can be proven that breast milk is the best and most ideal food for babies. For mothers who are breastfeeding babies, smooth milk is very important to meet the baby's needs. However, after going through the delivery process, most post partum mothers cannot produce breast milk because the milk does not come out.This study aims to identify the implementation of oxytocin massage to increase milk production in motherspost partum. In this study the methods used were interviews and observation.The results of this case study showed that before the oxytocin massage was carried out, the mother's milk production was carried outpost partum less increased and after oxytocin massage the production of breast milk in the motherpost partum increases, it can be obtained the result that there is a significant influence and increase in breast milk after oxytocin massage.it can be concluded that the application of the implementation of Oxytocin Massage has a significant effect on increasing the mother's milk productionPost Partum.can be a reference for writers in the future in facilitating the production of breast milk when they become mother